Formation of surface coatings on volcanic ejecta at four volcanoes in Costa Rica - Groenesteijn, K. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme | Agricultural University Wageningen, Wageningen (Países Bajos) | Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
7 fig. 4 tab. 36 ref. También como: Field Report - Atlantic Zone Programme (CATIE); no. 158